2000
DOI: 10.1046/j.1365-2443.2000.00307.x
|View full text |Cite
|
Sign up to set email alerts
|

Temporal and selective association of multiple sigma factors with RNA polymerase during sporulation in Bacillus subtilis

Abstract: Background: During sporulation in Bacillus subtilis, an asymmetric division produces two cells, a forespore and mother cell, with which follow different developmental paths. The highly ordered programme of temporal and spatial gene activation during sporulation is governed by the principal RNA polymerase holoenzyme (Es A ) and alternative holoenzyme forms containing the developmental sigma factors s H , s

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
63
0

Year Published

2003
2003
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 69 publications
(66 citation statements)
references
References 24 publications
3
63
0
Order By: Relevance
“…Polyclonal anti-Spo0A antibodies (Fujita 2000) were used for the detection of Spo0A and Spo0A*. Polyclonal GFP antibodies (Rudner and Losick 2002) were used for the detection of GFP-tagged KinA.…”
Section: Immunoblot Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…Polyclonal anti-Spo0A antibodies (Fujita 2000) were used for the detection of Spo0A and Spo0A*. Polyclonal GFP antibodies (Rudner and Losick 2002) were used for the detection of GFP-tagged KinA.…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…Polyclonal GFP antibodies (Rudner and Losick 2002) were used for the detection of GFP-tagged KinA. Polyclonal A antibodies (Fujita 2000) were used for the detection of A .…”
Section: Immunoblot Analysismentioning
confidence: 99%
“…Recent studies have shown that core RNA polymerase and s A levels remain constant during the transition from vegetative growth to sporulation (Fujita, 2000), and several lines of evidence suggest that s A -directed transcription takes place and is important even at late stages of sporulation (Fujita, 2000;Fukushima et al, 2003;Li & Piggot, 2001;Ohashi et al, 2003). A metabolic-pathwayoriented inspection of the temporal expression pattern revealed that certain classes of housekeeping genes continued to be expressed at a high level during sporulation, at least until 150 min after the initiation of sporulation.…”
Section: Differentiation Of the Compartment-specific Sporulation Regumentioning
confidence: 99%
“…The rabbit polyclonal antibodies that bind to A and Spo0A (Fujita 2000) were used at 1:10,000 and 1:5000 dilutions, respectively.…”
Section: Immunofluorescence Microscopymentioning
confidence: 99%